EXPLORING THE INTEGRATION OF GENDER GAP AND FINANCIAL LITERACY CONCEPT: A TREND PUBLICATION - Suziraha Dzulkepli; Shariah Bagam Abdul Rahman; Mohd Afiq Ab Jalil, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
This bibliometric analysis investigates research trends and collaborative networks in the area of "Gender Gap and Financial Literacy," highlighting key findings and thematic progressions in the field. As financial literacy significantly impacts personal economic well-being, understanding gender disparities within this context has become increasingly relevant, especially amid global discussions on financial inclusion and gender equity. However, limited studies synthesize the broader scope of this research, revealing a gap in identifying collaborative patterns and major themes that shape academic discourse. This study addresses this by utilizing Scopus Analyzer and VoSviewer software to map the research landscape. From a dataset of 1,041 documents, keyword co-occurrence and co-authorship analyses were conducted to identify central themes, influential countries, and major keywords shaping the discourse. Results show a significant concentration on terms such as “financial literacy,” “gender gap,” and “financial inclusion,” underscoring a central focus on gender disparities in financial knowledge and access. The United States, United Kingdom, and Australia emerged as leading contributors, with notable collaborative networks extending across diverse global regions. Furthermore, keywords related to health, social issues, and education, including “COVID-19,” “inequality,” and “higher education,” indicate that global events and socioeconomic factors intersect substantially with financial literacy research. The findings emphasize a growing, interdisciplinary focus on gender and financial literacy, with increasing global collaboration aimed at advancing understanding and promoting gender-inclusive financial education. This study provides a comprehensive view of the research landscape, identifying key areas for future investigation to address persistent gaps and enhance gender equality in financial literacy.